CAK-independent Activation of CDK6 by a Viral Cyclin - Kaldis, Philipp (The American Society for Cell Biology, 2001)
In normal cells, activation of cyclin-dependent kinases (cdks) requires binding to a cyclin and phosphorylation by the cdk-activating kinase (CAK). The Kaposi's sarcoma-associated herpesvirus encodes a protein with similarity to D-type cyclins. This KSHV-cyclin activates CDK6, alters its substrate specificity, and renders CDK6 insensitive to inhibition by the cdk inhibitor p16(INK4a). Here we investigate the regulation of the CDK6/KSHV-cyclin kinase with the use of purified proteins and a cell-based assay. We find that KSHV-cyclin can activate CDK6 independent of phosphorylation by CAK in vitro. In addition, CAK phosphorylation decreased the p16(INK4a) sensitivity of CDK6/KSHV-cyclin complexes. In cells, expression of CDK6 or to a lesser degree of a nonphosphorylatable CDK6(T177A) together with KSHV-cyclin induced apoptosis, indicating that CDK6 activation by KSHV-cyclin can proceed in the absence of phosphorylation by CAK in vivo. Coexpression of p16 partially protected cells from cell death. p16 and KSHV-cyclin can form a ternary complex with CDK6 that can be detected by binding assays as well as by conformational changes in CDK6. The Kaposi's sarcoma-associated herpesvirus has adopted a clever strategy to render cell cycle progression independent of mitogenic signals, cdk inhibition, or phosphorylation by CAK.